Work-life balance for transnational skilled workers in Sweden. (1st January 2020) - Ivana, Greti-Iulia
Abstract : In the context of globalisation, increased mobility and transnational travelling, long-distance friendships, romantic partnerships and family ties are becoming more and more common. Against this backdrop, this article focuses on highly skilled employees coming from Romania to Sweden and how they construct their work-life balance there. It analyses the work-life systems of highly skilled migrants in relation both to their co-present and long-distance bonds and overreliance on work networks of contacts, as well as investigating the relation between a particular work-life balance and highly skilled transnational workers' adoption of serial or circular migration. In doing so, this research asks how the work-life balance of highly skilled migrants can be understood from a life-course standpoint. The originality of this article comes from the interest in the work-life of transnational workers of both genders and of different family configurations, when most research on the topic of work-life balance still focuses almost exclusively on women and tensions between professional demands and traditional family lives.